Potensi Jamur Perakaran sebagai Agens Pengendalian Hayati Penyakit Moler (Fusarium oxysporum f.sp. Cepae) pada Bawang Merah - Andhika Wahyu Nugroho; Hadiwiyono Hadiwiyono; Sudadi Sudadi (Agrosains : Jurnal Penelitian Agronomi, 2015)
Desease that often occurs on the shallot is moler caused by Fusarium oxysporum f. sp. cepae (FOCe). This research was conducted to studied the potential of root-colonizing fungi to suppres moler disease on shallot. The researchs were divided into two steps that were laboratory test and screen house test used Completely Randomized Design (CRD). The treatments in screen house test were the combination of four fungi that had best capability to inhibit growth of FOCe. Each treatment was repeated three times. The result showed that root-colonizing fungi could reduce the moler disease but haven’t affect significantly growth component of shallot. Lowest disease intensity was 20% on the combination of AJ01, AJ12, AJ17, AJ18. Root-colonizing fungi have potention to decrease Moler disease.